1997
DOI: 10.1152/ajpgi.1997.272.2.g246
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-independent protein kinase C isoforms may modulate parietal cell HCl secretion

Abstract: Although activation of adenosine 3',5'-cyclic monophosphate by histamine and of Ca2+-dependent signaling pathways by cholinergic agonists is a generally recognized mechanism for increasing parietal cell HCl secretion, the role of protein kinase C (PKC) in this process is controversial. In this study, acid-secretory responses of gastric glands from rabbits [measured as accumulation of aminopyrine (AP)] were found to be relatively resistant to the PKC inhibitors calphostin C, chelerythrine chloride, staurosporin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 0 publications
3
29
0
Order By: Relevance
“…The complete antagonization by Go¨6976 of the TPA-dependent inhibition of H + secretion revealed the suppressive action of PKC-a. Recently, it has been reported that Go¨6976 (100 nM) had no detectable effect on the carbachol-stimulated AP uptake of rabbit gastric glands (Chew et al, 1997). Although comparing physiological data of parietal cells to gastric glands is only preliminary, we also observed that Go¨6976 at 100 nM had no significant effect on carbachol-induced H + secretion.…”
Section: Discussionsupporting
confidence: 42%
See 3 more Smart Citations
“…The complete antagonization by Go¨6976 of the TPA-dependent inhibition of H + secretion revealed the suppressive action of PKC-a. Recently, it has been reported that Go¨6976 (100 nM) had no detectable effect on the carbachol-stimulated AP uptake of rabbit gastric glands (Chew et al, 1997). Although comparing physiological data of parietal cells to gastric glands is only preliminary, we also observed that Go¨6976 at 100 nM had no significant effect on carbachol-induced H + secretion.…”
Section: Discussionsupporting
confidence: 42%
“…In rabbit parietal cells Go¨6976 is assumed to be specific to PKC-a, since other calcium-dependent PKC isoenzymes were not detected by specific antibodies (Nandi et al, 1996;Chew et al, 1997). Selective inhibition of PKC-a by Go¨6976 increased carbachol-evoked H + release up to about one-third.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coronin se was initially identified as pp66, a cholinergically regulated, PKC-dependent phosphoprotein in the HCl-secreting gastric parietal cell (11,12). In this study, we present evidence that pp66/coronin se is primarily located in an intracellular canalicular region of parietal cells, which is the site of active HCl secretion.…”
Section: From the Institute Of Molecular Medicine And Genetics Medicmentioning
confidence: 64%